Milking extracellular vesicles for health benefit using a multi-omics approach - Santoro, Jessie (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2023)
Milk is remarkable source of nutrients (i.e., proteins, fat, and sugars) and extracellular vesicles (EVs). EVs are tiny vesicles release by cells into all biofluids including milk. Milk EVs have been gathered huge attention recently for their scalability and non-toxic effect. Milk EVs have been separated and characterised from different species such as human, cow, goat, horse etc. Furthermore, extracellular vesicles (EVs) in milk contribute to regulate biological processes and cellular communication. The first aim of this project was to establish a process for EVs separation from milk that could be applied to multiple milk sources. The intention was to find a method that would result in enriched EVs that were not contaminated with milk-derived proteins, because proteins like casein micelle have overlapping size as EVs. For this purpose, commercial milk was used. We investigated different milk pre-treatment, attempting to remove these contaminants, and two techniques for EVs separation, differential ultracentrifugation and density gradient ultracentrifugation. We discovered that acid pre-treatment coupled with density gradient ultracentrifugation was the optimal solution to obtain enriched EVs samples with minimal contamination. Raw milk at different stages of the lactation has variable composition in colostrum (COL), known as liquid gold, first milk (FM) and mature milk (MM). Milk was collected from three different Holstein-Friesian cows; COL after 24hrs, FM after 7 days and MM and then EVs were separated and characterised. We observed that COL and FM are highly enriched in EVs compared to mature milk; particularly colostrum samples had the highest concentration of EVs which decreased throughout the lactation period. Particularly, bovine milk is used essentially for the manufacture of infant milk formula, used as the best alternative of human milk. However, bovine milk is subjected to severe treatments during industrial manufacturing of infant milk formula. Thus, our objective was to investigate if loss of EVs may occur at some stages of milk processing by the dairy industry. Indeed, we observed that heat treatments had detrimental consequences on EVs. EVs had disrupted structure and atypical morphology, while EVs yield was also significantly affected. Considering that, we are aware that millions of mothers worldwide are not breastfeeding. Therefore, we compared EVs characteristics in commercial IMF (liquid and powder formula) versus human milk (20 donors). EVs are transporters of important cargo such as proteins, nucleic acid and metabolites. Thus, human milk EVs contain cargo which have been associated with immune modulatory activity involved in shaping the newborn immune system. By investigating EVs quantity and quality from IMF and HM, we discovered that IMF had significant (p< 0.0001) lower concentration of EVs/particles. Using a multi-omics approach, we investigated the proteomics, metabolomics, and transcriptomics profile of milk EVs from infant milk formula and human milk. Mass spectroscopy analysis revealed that IMF EVs had lower concentration of 4 proteins (BTN1A1, CD36, SLC34A2, FABP3) in common with HM EVs, in which higher amount of proteins were detected. Similarly, for the metabolomic profiling of infant milk formula EVs compared to human milk EVs, we detected metabolites (i.e., human milk oligosaccharides, free amino acids, and nucleotides) associated with development of intestine and the gut microbiota, growth and immune development, which were all less enriched in IMF EVs in comparison with HM EVs. Subsequently, we selected miRNAs known to be the most abundant in milk EVs and associated with immunoregulatory function and demonstrated that they (miR-200a-3p, miR-148a-3p, miR- 200a-3p, miR-151a-5p, miR-148–3p, miR-30b-5p and miR-182–5p) had significantly lower levels in IMF EVs compared to HM EVs. Overall, milk EVs have the potential to be a powerful tool for improving IMF, which might reduce the risk of obesity, diabetes, and cardiovascular diseases in adulthood for artificially fed infants. In fact, the role of breast milk in the modulation of the infant’s immune system through the transfer of personalised microbial and immune factors is a topic of high scientific and commercial interest. Moreover, the essential role of milk in infant and adult nutrition along with the abundance of EVs, makes milk EVs a particular candidate of interest with the potential therapeutic application. Their abundance and non-toxic nature make milk EVs an efficient vehicle for drug delivery.
APPROVED